Pengaruh penambahan senyawa ekstrak kulit jeruk (Citrus sp.) terhadap sifat fisika plastik biodegradable dari ubi kayu dengan senyawa aditif gula jagung - Dona Intan Rezki (PILLAR OF PHYSICS, 2016)
The materials used today to package food and drink one of which is plastic. Over time, the plastic needs increasing in many areas of life. On the other hand, the use of plastics as packaging materials face many environmental problems, which can not be decomposed by microbes in the soil. This resulted in the accumulation of plastic waste that cause air pollution, environmental damage and also have a negative effect on human life. Because of these problems, need to be overcome to make plastics that are environmentally friendly and do not cause pollution, the biodegradable plastic. Biodegradable plastics in this study with the addition of orange peel extract compounds of 0%, 10%, 15%, and 20%. Tests were performed to obtain the value of the mechanical properties and degradation of plastics biodegrdable cassava with variation of orange peel extract compounds are as follows: increased tensile strength values for the addition of orange extract compounds from 10% -15 and decreases in increments of 20%, as well as the flexural strength . While the ability of degradation increases with increasing amount of orange peel extract compounds